Merytoryczne orzekanie sądów administracyjnych w przypadku uwzględnienia skargi na bezczynność organów lub przewlekłe prowadzenie postępowania - Chmielewski, Jan (PRAWO i WIĘŹ, 2026)
In the current legal system, regulations provide for a cassation model of judicial control of administration, although a reformatory component of adjudication by administrative courts is also visible here. It usually appears in the form of individual regulations wherever the legislator seeks to streamline proceedings before administrative courts and – more importantly – to maximize the effectiveness of judicial protection of the individuals. One of such regulations is the power granted to the administrative court to rule on the existence or non-existence of a right or obligation in the event of upholding a complaint about inaction or excessive length of proceedings by a public administration body (Art. 149 § 1b of the Act – Law on Administrative Court Procedure). In the judicial practice of administrative courts, a position has developed in favour of a narrow understanding of this regulation. The author of this text argues for its broad approach, which is justified by recognized methods of interpretation of the cited norm and ensures fuller protection of subjective rights. According to this concept, it is incorrect to limit the application of Art. 149 § 1b of the Act – Law on Administrative Court Procedure to inaction or delay occurring in the case of only one form of administrative action, referred to in Art. 3 § 2 item 4 of the Act – Law on Administrative Court Procedure. On the contrary, the scope of regulation of Art. 149 § 1b of the Act – Law on Administrative Court Procedure should also include the passivity of administrative bodies in proceedings intended to issue, among others, an administrative decision, an administrative resolution or in cases of written interpretations of tax law provisions.